When Teachers Go the Extra Mile Determinants of Organisational Citizenship Behaviour of Schoolteachers in Jaffna ,Sri Lanka - Gnanarajan, A.H. (My University, 2021)
Organisational citizenship behavior (OCB), an extra role vo1untary behavior of employees, has been found essential for an organization in several ways, and educational organizations too have found it beneficial towards their holistic development. The researcher, having been conscious of the “low morale” and the attitudinal decline of teachers as pointed out by the National Education Commission and the World Bank, embarked on a preliminary qualitative study to identify the existing concerns related to attitudinal deterioration of teachers in the Jaffna District drawing special attention to their OCB. The findings of the preliminary study and the subsequent exploration of the extant literature, which revealed inconsistent research findings and a paucity of OCB studies in educational contexts, led the researcher towards the formulation of the research problem : the teachers' OCB had been on the decline, and the factors like work interference with family (WIF), perceived organizational support (POS), teachers' self-efficacy, personal values of teachers, student behaviour patterns(SBP), and the teachers' pupil control ideology (PCI) seemed to have an effect on OCB. In order to delve deeper and scientifically validate the potential correlations, the present study was carried out. Structural equation modeling was employed using AMOS with WIF, self-efficacy, student behaviour patterns, and values of teachers such as benevolence, achievement, self-direction and conformity, as independent variables and OCB as the dependent variable, whilst POS and PCI were tested in multi group analysis for their moderating effects on the WIF-OCB and SBP-OCB relationships respectively. Data were collected using self-report questionnaires from 572teachers from the Jaffna District. The results revealed that teachers' propensity to perform OCB was affected neither by their work interference with family nor by their students' behavior patterns. However, the teachers who had less perceived support from their schools were negatively affected by their work inference with family in their propensity to perform OCB, and those who were custodial in their pupil control ideology were negatively affected by their students' behaviours in demonstrating OCBs. A significant positive relationship was found between teachers' self-efficacy and their OCB. As for teachers' value orientations, the teachers who were benevolentce-driven displayed more OCBs, and those driven by achievement, self-direction and conformity did not have any association with their levels of OCBs. This study makes significant theoretical contributions to the growing corpus of scholarly knowledge, and offers pragmatic recommendations to the policymakers and practitioners in the fields of human resource management and education. A unique endeavour that no research in the past has attempted to achieve is the investigation of the SBP-OCB link with the moderating effects of PCI on the same, and of POS on the WIF-OCB link - which acknowledges the study's originality.
Keywords: Organisational citizenship behavior; Teacher OCB; Work interference with family; Perceived organizational support; Self-efficacy; Human values; Student behavior patterns; Pupil control ideology